Effect of Professionality and Motivation on Audit Quality in Public Accounting Firm in Jakarta Area - Saprudin Saprudin (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
This research examines whether professionalism and motivation influence audit quality. The auditor must always be professional in conducting audits and have high motivation in the work so that the quality of the financial statements audited receives strong public trust. The samples in this study were auditors who worked in the Public Accountant Office (KAP) in Jakarta with 83 respondents and companies using audit services of the Public Accounting Firm with a total of 17 respondents, so that the total sample used amounted to 100 respondents. The sampling method taken was purposive sampling. A questionnaire is a tool used to measure variables. The analysis technique in this study uses multiple linear regression analysis. The results of hypothesis testing show that professionalism has a significant effect on audit quality, and motivation also has a significant effect on audit quality. Based on the simultaneous analysis shows that professionalism and motivation simultaneously (together) influence the audit quality..